Pengaruh Metode Glenn Doman (Tahap 1 dan 2) terhadap Perkembangan Komunikasi Anak Autisme - Haifa Wahyu; Betrianita Betrianita; Melati Tridita Pramesti; Padila Padila (Jurnal Keperawatan Silampari, 2018)
This study aims to determine the effect of the Glenn Doman methods stages 1 and 2 on the development of thinking communication in children with autism at the Bengkulu Autism Center. The research design used was quasi experiment, with the design used was two groups before after or pre-test and post test group design. The results showed that in the univariate analysis the majority of respondents aged 3-4 years with the majority of male sex with the ability to speak in the control group and the treatment group before being given glenn doman therapy stages 1 and 2 were quite capable. And the development of communication in the majority treatment group increased to be able. In bivariate analysis, it was known that the value of p v 0,000 <0.05. Conclusion, there is a significant influence of stage 1 and 2 glenn doman therapy on the development of communication of children with autism at Bengkulu Autis Center. Keywords: Autism, Glenn Doman